Spatially controlled electrostatic doping in graphene p-i-n junction for hybrid silicon photodiode. (December 2018) - Li, Tiantian; Mao, Dun; Petrone, Nick; Grassi, Robert; Hu, Hao; Ding, Yunhong; Huang, Zhihong; Lo, Guo-Qiang; Hone, James; Low, Tony; Wong, Chee; Gu, Tingyi
Abstract Sufficiently large depletion region for photocarrier generation and separation is a key factor for two-dimensional material optoelectronic devices, but only a few device configurations have been explored for a deterministic control over the space charge region area in graphene with convincing scalability. Here we investigate a graphene-siliconp-i-n photodiode defined in a foundry processed planar photonic crystal waveguide structure, achieving visible—near-infrared, zero-bias, and ultrafast photodetection. Graphene is electrically contacting to the wide intrinsic region of silicon and extended to thep ann doped region, functioning as the primary photocarrier conducting channel for electronic gain. Graphene significantly improves the device speed through ultrafast out-of-plane interfacial carrier transfer and the following in-plane built-in electric field assisted carrier collection. More than 50 dB converted signal-to-noise ratio at 40 GHz has been demonstrated under zero bias voltage, the quantum efficiency could be further amplified by hot carrier gain on graphene-i Si interface and avalanche process on graphene-doped Si interface. With the device architecture fully defined by nanomanufactured substrate, this work demonstrates post-fabrication-free two-dimensional material active silicon photonic devices. Hybrid photodiodes: graphene/siliconp -i -n junctions by electrostatic doping A hybrid optoelectronic junction design with graphene on silicon enables high quantum efficiency and ultrafast response. A team led by T. Gu at the University of Delaware developed a device configuration based on an in-planep -i -n junction made of graphene on a silicon photonic crystal waveguide. The photonic crystal is used to enhance the photoresistivity, whereas graphene plays the role of electrical contact to the intrinsic region of silicon whilst also extending to thep - andn -doped regions, and acts as photocarrier conducting channel. The carrier transport channel is dominated by drift-current, which is instrumental to high external quantum efficiency. The latter is improved eight times on average over the visible range, if compared to a control device based on bare silicon.